The Influence of Celebrity Endorsers, Brand Awareness, and Product Variety on Scarlett Whitening's Purchase Decisions In Ambon City - Erlinda Tehuayo; Rukmuin Wilda Payapo; Trisna Sary Lewaru; Asmaniar Drakel (ARRUS Journal of Social Sciences and Humanities, 2024)
This research is a quantitative descriptive research. The population used in this study was all consumers who had already purchased and used Scarlett Whitening. Sampling was carried out by purposive sampling technique with a sample of 160 respondents. Data was collected using questionnaires. Data analysis in this study used Multiple Linear Regression. The results of this study show that Celebrity Endorsers have a positive and significant influence on the Purchase Decision of Scarlett Whitening in the city of Ambon. Furthermore, Brand Awareness has a positive and significant effect on the Purchase Decision of Scarlett Whitening in the city of Ambon and Product Variations have a positive and significant effect on the Purchase Decision of Scarlett Whitening in the city of Ambon